Suksesi Bisnis Keluarga/Bisnis Kecil dan Keberhasilan Bisnisnya - Tuhardjo, Tuhardjo (Universitas Brawijaya, Indonesia, 2011)
A familly or small business as one in which both ownership and policy making are dominated by members of an